THE INFLUENCE OF LIQUIDITY, PROFITABILITY ON FINANCIAL DISTRESS IN FOOD AND BEVERAGE COMPAINES ON THE IDX - Sulmiah Sulmiah; Mariam Makmur; Usman Rahman (Universitas Ichsan Sidenreng Rappang, 2024)
Financial distress conditions are more important than bankruptcy, because companies will definitely experience financial distress conditions first before experiencing bankruptcy. The research design used in this research is causal correlation/associative. This research uses secondary data in the form of quantitative data. The aim of this research is to test the effect of liquidity and profitability on financial distress using the t test and F test. The sample used in this research was 35 in the 2021-2022 period using the purposive sampling method. Based on the results of research conducted on food and beverage sub-sector manufacturing companies that are Go-Public on the Indonesia Stock Exchange in 2021-2022, it can be concluded as follows: The Effect of Liquidity on Financial Distress. The results of the partial test (t-test) show that the current ratio is not The effect on financial distress is different from the hypothesis proposed that liquidity has an effect on financial distress, which is not proven. The effect of profitability on financial distress. The partial test results (t-test) show that Return On Assets has a positive and significant effect on financial distress. The Simultaneous Effect of Liquidity and Profitability on Financial Distress. Simultaneous test results (F) show that liquidity and profitability together have a positive and significant effect on financial distress. Based on the findings, it can be said that companies that are able to generate good profits have a low chance of financial distress, and vice versa. Therefore, it will reflect good financial conditions and provide a positive reaction for potential investors who will invest their capital.